Viscoelastic behavior of gels obtained from five cultivars of quinoa at altitude gradient - Polo-Muñoz, María Paula; Garcia-Parra, Miguel Ángel; Roa-Acosta, Diego Fernando (Frontiers in Sustainable Food Systems, 2023)
Background: Quinoa consumption has created a challenge for producers and food processors. They need to study new cultivars and the functional properties of quinoa flours. Methods: The structural and rheological properties of six quinoa cultivars (Titicaca, Blanca real, Soracá, Pasankalla, Puno and Nariño) grown at different altitudes were studied using Fourier Transform Infrared spectroscopy (FTIR) and dynamic oscillatory tests. The FTIR spectra revealed differences in the protein and starch structures among the cultivars, which could be related to their adaptation to different environmental conditions. The rheological analysis showed that the quinoa gels exhibited viscoelastic behavior, with a predominance of the elastic component (G') over the viscous component (G''). The linear viscoelasticity range was determined by applying a strain sweep test (0.001 to 100%) at a constant frequency of 5 Hz. The frequency sweep test (0.01 to 100 Hz) at a constant strain amplitude of 0.1% within the linear regime was used to obtain the storage modulus (G'), the loss modulus (G'') and the complex viscosity (η*). Results: The Burgers model was fitted to the experimental data, and the four parameters (η1, η2, R1 and R2) were obtained for each cultivar. The results showed that the cultivar, the altitude and their interaction had significant effects on the rheological properties of the quinoa gels. The cultivars grown at higher altitudes tended to have higher G', G'' and η* values than those grown at lower altitudes, indicating a stronger gel network. The cultivars also differed in their relaxation times, with Titicaca and Blanca real having the shortest and longest times, respectively. These differences could be attributed to the variations in the protein and starch structures of the quinoa flours, as well as the water absorption and gelation properties of the cultivars. Conclusions: The viscoelastic behavior of gels is influenced by the structural conformation of their components, such as proteins and starch. These components provide stiffness and elasticity to the gels. The structural conformation can change depending on the environmental conditions and the phenotypic characteristics of the components.